Mulheres encarceradas por tráfico de drogas : reflexões acerca da estrutura social e do protagonismo individual - Gil, Bruna Laudissi (2015)
This dissertation discusses the involvement of women in crime. To achieve this objective, female prisoners by the involvement with drug trafficking were interviewed in a women's prison in the state of Rio Grande do Sul. The interviews were conducted in order to know the social, economic and family background of these women; to investigate their motivations for joining in the activity; to understand the meanings given by them to the prison situation; to know the mechanisms of exclusion that act on them; to understand the violence suffered by them and to investigate the protagonism during their life histories. For the analysis of the interviews was used the Critical Discourse Analysis, which aims to question how certain discourse structures are used in the reproduction and in the defense of social domination and power of the hegemonic social groups (Van Dijk, 2005). From this research were developed two empirical articles. The first of them discusses the way which the social structure is reflected in the trajectories of these women. Therefore, we discuss the various forms of violence which affect mainly the poorest social groups, as well as the social rights constitutionally guaranteed such as education and work, often overlooked to this population. The second article reflects the female crime, highlighting the power of decision and the protagonism of incarcerated women. Theoretical discussions at this time, approach the way women are constantly victimized within the criminological literature as well as the agency existent in the choices of these women, including in the case of transgressive choices. Finally, the article deals with the dialectic existent between subject and social structure, emphasizing that the subject is, at the same time, product and producer of their reality. The involvement of women in crime is a complex phenomenon that needs studies to contemplate, especially from the gender lens, and that look for to emphasize the protagonism and the agency of these women. This work enabled us to move forward in these studies. The challenge was to build a way of looking at the female criminality joining the reflections of the two articles, in other words, looking for consider simultaneously the social context and the individual protagonism.